Efficient Rule-Based Inferencing for OWL EL. - Krötzsch, M (IJCAI/AAAI, 2011)
We review recent results on inferencing for SROEL(x), a description logic that subsumes the main features of the W3C recommendation OWL EL. Rule-based deduction systems are developed for various reasoning tasks and logical sub-languages. Certain feature combinations lead to increased space upper bounds for materialisation, suggesting that efficient implementations are easier to obtain for suitable fragments of OWL EL.